Mimicking Hypoxic-Ischemic Encephalopathy in a Newborn with 21q Deletion Originating from Ring Chromosome 21 - Ja Un Moon; Sook Kyung Yum (MDPI AG, 2023)
Partial deletion of the long arm (q) in chromosome 21 is an extremely rare condition with various phenotypes, including microcephaly, neurodevelopmental delay, dysmorphic features, and epileptic seizures. Neonatal hypoxic-ischemic encephalopathy (HIE) is an encephalopathy associated with a hypoxic-ischemic event in the brain where seizures usually occur in the earliest days of life. Neonatal encephalopathy is a distinct entity resulting from metabolic disorders, congenital infections or genetic abnormalities that could often mimic HIE features, leading to a misdiagnosis of HIE. Here, we present a case of a newborn who was initially misdiagnosed with HIE due to HIE-like features, and eventually was diagnosed to have a de novo ring chromosome 21 with 21q microdeletion. Clinical findings, including severe hypotonia with respiratory/feeding difficulties and intractable seizures, and radiologic findings of ischemic encephalopathy were discovered. Subsequent atypical findings of the clinical presentation ultimately led to her undergoing genetic testing confirming that she had a neonatal encephalopathy with a genetic abnormality. Our case highlights the importance of identifying non-HI neonatal encephalopathy by careful and structured evaluation for current history with a clinical course and a multidisciplinary approach including genetic testing, to provide an accurate diagnosis, treat curable inherited disorders, and develop future genetic counseling.